Metabolic syndrome does not impact long‐term survival in patients with acute myocardial infarction after successful percutaneous coronary intervention with drug‐eluting stents. Issue 5 (15th November 2013) - Won, Ki‐Bum; Kim, Byeong‐Keuk; Chang, Hyuk‐Jae; Shin, Dong‐Ho; Kim, Jung‐Sun; Ko, Young‐Guk; Choi, Donghoon; Ha, Jong‐Won; Hong, Myeong‐Ki; Jang, Yangsoo
<x xml:space="preserve">Abstract</x> Objective This study aimed to evaluate long‐term survival according to the presence of metabolic syndrome (MS) in patients with acute myocardial infarction (AMI) undergoing successful percutaneous coronary intervention (PCI) with drug‐eluting stents (DES). Background Despite the significance of coronary reperfusion in AMI, the prognostic impact of MS has been investigated under inconsistent reperfusion therapy in AMI patients. Methods and Results Three‐year clinical outcomes, including all‐cause death and the composite of cardiac death or myocardial infarction, were evaluated according to MS status for 963 patients with AMI treated with successful PCI with DES. This study included 494 subjects with MS (51%) and 469 subjects without MS (49%). The incidence of multivessel disease and the mean number of implanted stents were significantly higher in patients with MS than in patients with non‐MS. The occurrence of all‐cause death (5.9% vs. 6.4%, P = 0.789) and the composite outcomes (5.1% vs. 6.2%, P = 0.485) did not differ significantly between patients with and without MS. Cox regression models revealed that MS had no significant impact on all‐cause death (hazard ratio [HR] 0.91; 95% confidence interval [CI] 0.55–1.52; P = 0.726) or the composite outcomes (HR 0.81; 95% CI 0.48–1.39; P = 0.448). Obesity was associated with a decreased risk of all‐cause death and the composite outcomes among all MS components. Conclusions No difference was observed in long‐term survival according to the presence of MS in patients with AMI after successful PCI with DES. This suggests that reperfusion therapy using PCI with DES is equally beneficial in patients AMI with and without MS. © 2013 Wiley Periodicals, Inc.